2022
DOI: 10.1021/acs.analchem.1c05384
|View full text |Cite
|
Sign up to set email alerts
|

Biohybrid Tongue for Evaluation of Taste Interaction between Sweetness and Sourness

Abstract: The past decade has witnessed tremendous progress achieved in taste research, while few studies focus on interactions among taste compounds. Indeed, sweeteners and acidulants are commonly used food additives, and sweet−sour mixtures always provide improved tastes. For example, sensory studies have shown that sourness suppresses sweetness. However, the degree of sweetness suppression by sourness is difficult to evaluate quantitatively and objectively. Therefore, we propose a biohybrid tongue that is constructed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…With the increase of the PP concentration and CA added, the sweet and sour tastes gradually grew stronger, which effectively inhibited the bitter taste. However, the sour taste basically had no inhibiting effect on the sweet taste [ 47 ], and the sweet had a soothing effect on the sour taste. Umami is a signal of protein.…”
Section: Resultsmentioning
confidence: 99%
“…With the increase of the PP concentration and CA added, the sweet and sour tastes gradually grew stronger, which effectively inhibited the bitter taste. However, the sour taste basically had no inhibiting effect on the sweet taste [ 47 ], and the sweet had a soothing effect on the sour taste. Umami is a signal of protein.…”
Section: Resultsmentioning
confidence: 99%
“…In the early twenty-first century, another important development of the bioelectronic tongue was presented to analyze complex mixtures of chemical compounds and identify individual compounds that are not available using traditional methods. [13][14][15][16] Bioelectronic tongues are based on a variety of recognition elements, [17][18][19][20][21][22][23] such as nucleic acids, proteins, antibodies, cells, and taste receptors. A key feature of bioelectronic tongues is their high selectivity and sensitivity.…”
Section: Taste Sensorsmentioning
confidence: 99%
“…This is because the biological unit in biohybrid sensors can sense and respond to a wider range of weak physiological stimuli with higher specificity [6] and can integrate with the host through vascularization to create a more physiological connection to the external evaluation units. Recent in vitro studies have shown the potential of biohybrid sensors for applications such as odorant [7] and taste [8] sensing, directional chemical source detection, [9] infrared detection, [10] and drug evaluation. [11,12] However, to extend these applications to in vivo microenvironments, new strategies are needed that can meet the requirements of the host tissue, the biological sensing, and the nonbiological readout units.…”
Section: Introductionmentioning
confidence: 99%